Relationships Among Microbial Communities, Maternal Cells, Oligosaccharides, and Macronutrients in Human Milk. (August 2017) - Williams, Janet E.; Price, William J.; Shafii, Bahman; Yahvah, Katherine M.; Bode, Lars; McGuire, Mark A.; McGuire, Michelle K.
Background: Human milk provides all essential nutrients necessary for early life and is rich in nonnutrients, maternally derived (host) cells, and bacteria, but almost nothing is known about the interplay among these components. Research aim: The primary objective of this research was to characterize relationships among macronutrients, maternal cells, and bacteria in milk. Methods: Milk samples were collected from 16 women and analyzed for protein, lipid, fatty acid, lactose, and human milk oligosaccharide concentrations. Concentrations of maternal cells were determined using microscopy, and somatic cell counts were enumerated. Microbial ecologies were characterized using culture-independent methods. Results: Absolute and relative concentrations of maternal cells were mostly consistent within each woman as were relative abundances of bacterial genera, and there were many apparent relationships between these factors. For instance, relative abundance of Serratia was negatively associated with somatic cell counts ( r = –.47, p < .0001) and neutrophil concentration ( r = –.38, p < .0006). Concentrations of several oligosaccharides were correlated with maternally derived cell types as well as somatic cell counts; for example, lacto-N-tetraose and lacto-N-neotetraose were inversely correlated with somatic cell counts ( r = –.64, p = .0082; r = –.52, p = .0387, respectively), and relative abundance of Staphylococcus was positively associated with total oligosaccharide concentration ( r = .69, p = .0034). Complex relationships between milk nutrients and bacterial community profile, maternal cells, and milk oligosaccharides were also apparent. Conclusion: These data support the possibility that profiles of maternally derived cells, nutrient concentrations, and the microbiome of human milk might be interrelated.